Estimating distribution parameters of extreme event using TL-moment method - Nur Amalina Mat Jan, 1989- author; Ani Shabri; Fakulti Sains (2014)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2014